Doctor Who. The complete third series [videorecording (DVD)] - Lyn, Euros; Palmer, Charles; Clark, Richard (Television director); Strong, James (Television director); Harper, Graeme, 1945-; MacDonald, Hettie; Teague, Colin; Tennant, David, 1971-; Agyeman, Freema, 1979-; Tate, Catherine; Barrowman, John, 1967-; Andoh, Adjoa; et al. (BBC Video, 2 Entertain : BBC Worldwide Americas ; Distributed by Warner Bros. Entertainment, 2007)
The Doctor partners up with Martha Jones and embark on adventures through time and space, encountering strange lifeforms and protecting the Earth from invaders.